SISTEM MONITORING SERANGAN JARINGAN KOMPUTER BERBASIS WEB SERVICE MENGGUNAKAN HONEYPOT SEBAGAI INTRUSION PREVENTION SYSTEM - Inda Sari; Muh. Yamin; LM Fid Aksara (Informatics Engineering Department of Halu Oleo University, 2019)
Security is very important especially to maintain the integrity of data for internet service users. There are many ways to infiltrate computer networks, starting from just experimenting to trying to damage and steal important information on the server. One way to overcome this problem is by the existence of an attack prevention system or commonly referred to as the Intrusion Prevention System (IPS) so that an attack can not directly touch the data or files that others should not know.Honeypot is a system that is deliberately sacrificed in order to be attacked to obtain information from the activities of the attacker and to know the methods used in attacking a system. The results of attacks on the system can be displayed in a monitoring system and can also be displayed through a web service. The results obtained from this study that the creation of a web service -based computer network attack monitoring system uses a honeypot as an IPS successfully implemented. Attacks that enter through TCP ports are 33.96%, UDP 33.96%, and ICMP 32.07%.Keywords— Honeypot, Web Service, Intrusion Prevention System DOI : 10.5281/zenodo.2651714